Clinical reasoning: a 64-year-old man with history of meningitis presenting with proximal weakness of the arms - Karschnia, Philipp; Kaulen, Leon D.; Thon, Niklas; Bähring, Joachim (Neurology, 2022)
A 64-year-old man presented for evaluation of proximally pronounced weakness of the arms with preserved facial and lower extremity strength. Symptoms slowly developed over the last 2 years, and the patient's history was notable for severe Listeria monocytogenes meningitis 4 years before presentation, which was adequately treated with antibiotics. On examination, symptoms clinically reassembled man-in-the-barrel syndrome and localized to the cervicothoracic central cord. Blood analysis was unremarkable, and CSF analysis showed no recurrent or persistent infection. Spinal MRI revealed pockets of sequestered CSF from C3 to C4 and areas of CSF space effacement from C3 to T12. MRI findings were interpreted as cord tethering suggestive of adhesive arachnoiditis. CT myelogram showed insufficient contrast agent migration above T10 and contour irregularities of the conus medullaris, confirming the postulated pathomechanism of cord tethering. Final diagnosis was therefore cervicothoracic central cord damage due to cord tethering in the setting of postinfectious adhesive arachnoiditis following bacterial meningitis. The patient failed a course of pulsed methylprednisolone therapy, and symptoms progressed. Best supportive care was provided. The clinical presentation of adhesive arachnoiditis is variable, and advanced imaging techniques and invasive studies such as CT myelogram may be required to establish the diagnosis. Timely diagnosis is warranted as early surgical or medical therapy can improve symptoms.